The value of soaking shelled corn for finishing spring pigs on alfalfa pasture - Aubel, C.E. (Kansas Agricultural Experiment Station, 2011)
Soaking grain for pigs has been revived and an automatic and self-feeder that soaks grain is on the market. This experiment was to test that system of feeding corn. Two lots of nine pigs each were self-fed, free-choice, shelled corn and a mixed protein supplement as a basal ration. The treatment of the two lots varied only in that corn for lot 2 was soaked in water. The protein supplement fed both lots consisted of 4 parts tankage, 4 parts soybean meal, 1 part cottonseed meal, and 1 part alfalfa meal.
Keywords: Swine; Shelled corn; Alfalfa